#TITLE_ALTERNATIVE# - PERWIRANEGARA (NIM : 10208022); Pembimbing : Wahyu Srigutomo,Ph.D., HENDRA
Resistivity model is a kind of geophysical method intended to determine half surface resistivity distribution by doing measurement on the surface. Resistivity method used for studying underneath surface layers vertically by using VES (Vertical Electrical Sounding) method and horizontally by using CST (Constant Separation Transversing). Data which was taken by using 1D Schlumberger configuration will give information about apparent resistivity in every measurement point. Apparent resistivity values are mapped according to the arrays between AB/2=5 meter until AB/2= 1260 m. Apparent resistivity data was later inverted. Inverted results were then forward modeled back and produced true resistivity data according to the depth. Overlay results on apparent resistivity map showing traces of geothermal system at zone around hot spring manifestation. This was seen from low apparent resistivity zone at AB/2=350m, continued by mid apparent resistivity zone at lower array which shown by conceptual model of geothermal system. This was supported by cross section resistivity on line 8, which showed at low resistivity zone at Ã‚Â±300 m depth, while on line 8 passed by faults around manifestation zone which happen to be manifestation exit. Results on line 8 indicating there is a clay cap layer leads to the south east. Penetration capability for electric survey method is too shallow to detect geothermal source, causing the clay cap layer thickness cannot be predicted.